Off site and boundary external radiation exposures from the Cotter Uranium Mill located in Cañon City, Colorado - Townsend, Amanda, author; Johnson, Thomas, advisor; Brandl, Alexander, committee member; Rocca, Jorge, committee member (Colorado State University. Libraries, 2017)
Although many of the uranium mills in the United States have been decommissioned, the mill tailings remain and can pose health threats to those living nearby. Many studies have been done showing the relationship between radon exposure and lung cancer development for those living near a uranium mill, but it seems that little attention has been paid to the possible threat posed by exposure to gamma radiation from these tailings piles. Since 1979 the Cotter Uranium Mill in Cañon City, Colorado has been measuring external gamma exposure rates at the fence line, and at several offsite locations including the closest residence and the Shadow Hills Golf Course. These exposure rate measurements were tested against background and it has been shown that exposure rates above background exist at all locations except for the nearest residence. Assuming full time occupancy, the excess dose received by members of the public from these exposure rates do not exceed regulatory limits of 100 mrem/yr except at the entrance road of the mill, which was remediated in 2009. For a hypothetical person living in the area of highest exposure rate above background, their risk of developing a fatal cancer is only increased by 0.43%. These exposure rates were compared against the background values measured by the Cotter Corporation and published in their 2010 Environmental and Occupational Performance Report, ALARA Review and Annual Report on Remedial Action Plan Activities. It was later discovered that the background values published in this report were read from a dosimeter that was kept in lead shielding at an offsite location. This means that the background values are only transit values, and are not representative of the actual background. As such, a discussion of what justifies an appropriate background measurement as well as its effect on the results of this study are outlined. Lastly, correlation analysis was performed on the exposure rate data to determine if there was an underlying factor effecting all the exposure rates. It was found that a single factor is responsible for 60.28% of the variation in the exposure rates, but the factor affecting the data could not be determined. It was suspected that either precipitation values, cosmic radiation fluctuations, or radium-226 air concentrations may have affected the exposure rates, and, as such, correlation analysis was conducted. It was determined that no correlation exists between any of these variables and the exposure rates measured. The inability to determine the factor contributing to the fluctuation in exposure rates over the years provides opportunity for continued research.